Solving Socio-Financial Challenges of Contemporary Muslims in Nigeria Using Cash Waqf - Adenigba Atanda, Sikiru; Fatai Akanni, Adigun (Journal of Islamic Economic and Business Research, 2025)
Cash Waqf is an integral part of the Islamic Social Financial System, and its uniqueness significantly enhances the scope of Waqf practice in both the banking and non-banking sectors in Nigeria. It is one of the socio-financial tools used to address the challenges facing contemporary Muslims. There are problems of socio-financial issues among contemporary Muslims, which lead to poor health care, insecurity, poor access to education, etc. This paper aims to address the socio-financial challenges faced by contemporary Muslims in Nigeria using the concept of Cash Waqf. Qualitative and analytical methods are employed in the research to present facts and conduct an objective analysis. The qualitative method was employed to review existing works on the subject in sequence, while the analytical method helps to conduct proper analysis of Islamic financial models. The finding revealed that the Cash Waqf is viable and innovative, as it provides opportunities for many individuals to invest in the hereafter by finding holistic solutions to human problems. It makes available modern Models of Waqf in cash form that can be adopted by the Islamic Finance Sector and beyond. The paper concludes that there is a need to work on the Waqf institution, as it may provide humankind with many other career opportunities in the near future. It is recommended that the application of Cash Waqf and its models, in line with the principles, be made known to the general Muslim community while also raising awareness of the opportunities available. Additionally, the training of Waqf Managers should be enhanced to ensure effective utilization of the model.